Sources of information on monkeypox virus infection. A systematic review with meta-analysis - Darwin A. León-Figueroa; Joshuan J. Barboza; Mario J. Valladares-Garrido (BMC, 2024)
Abstract Background Monkeypox (Mpox) virus infection is a topic of growing interest today because of its potential public health impact and concern about possible outbreaks. Reliable and up-to-date sources of information that provide accurate data on its transmission, symptoms, prevention, and treatment are essential for understanding and effectively addressing this disease. Therefore, the aim of the present study is to determine the prevalence of sources of information on Mpox virus infection. Methods An exhaustive systematic review and meta-analysis was carried out using the information available in the PubMed, Scopus, Web of Science, Embase, and ScienceDirect databases up to August 3, 2023. The data were analyzed using R software version 4.2.3. The quality of the cross-sectional studies that formed part of this review was assessed using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) tool. In addition, a subgroup analysis was performed based on the study populations. Results Through electronic searches of five databases, a total of 1833 studies were identified. Twenty-four cross-sectional articles were included, with a total sample of 35,959 participants from 34 countries. The pooled prevalence of each of the included information sources was: social networks reached 59% (95% CI: 50-68%; 29,146 participants; 22 studies; I 2 = 100%; p < 0.01); the Internet was 61% (95% CI: 44-77%; 14,002 participants; 5 studies; I 2 = 100%; p < 0.01), radio reached 10% (95% CI: 07-13%; 8917 participants; 4 studies; I 2 = 93%; p < 0.01), television accounted for 24% (95% CI: 09-43%; 14,896 participants; 8 studies; I 2 = 100%; p < 0.01), and the combination of radio and television accounted for 45% (95% CI: 31-60%; 4207 participants; 7 studies; I 2 = 99%; p < 0.01); for newspapers, it was 15% (95% CI: 05-27%; 2841 participants; 6 studies; I 2 = 99%; p < 0.01), friends and relatives accounted for 19% (95% CI: 12-28%; 28,470 participants; 19 studies; I 2 = 100%; p < 0.01), the World Health Organization (WHO) accounted for 17% (95% CI: 07-29%; 1656 participants; 3 studies; I 2 = 97%; p < 0.01), the Centers for Disease Control and Prevention (CDC) accounted for 10% (95% CI: 03-21%; 2378 participants; 3 studies; I 2 = 98%; p < 0.01), and the combination of WHO and CDC websites accounted for 60% (95% CI: 48-72%; 1828 participants; 4 studies; I 2 = 96%; p < 0.01), and finally, scientific articles and journals accounted for 24% (95% CI: 16-33%; 16,775 participants; 13 studies; I 2 = 99%; p < 0.01). Conclusion The study suggests that people access a variety of information sources to gain knowledge about Mpox virus infection, with a strong emphasis on online sources such as social networks and the Internet. However, it is important to note that the quality and accuracy of information available from these sources can vary, underscoring the need to promote access to reliable and up-to-date information about this disease to ensure public health.